The association between periodontitis and arterial stiffening among the hypertensive middle-aged and elderly U.S. Population - CuiZhu Hu; HuanRui Zhang; GuoXian Qi; Wen Tian (Scientific Reports)
Abstract Arterial stiffening is an independent predictor of cardiovascular diseases, closely associated with hypertension and aging. Periodontitis, a chronic inflammatory disease caused by microbial imbalances, has been linked to systemic inflammation and endothelial dysfunction. This study aims to investigate the association between periodontitis and arterial stiffening in hypertensive individuals. Data utilized in this study were sourced from the 2009–2014 National Health and Nutrition Examination Survey (NHANES). A total of 3165 hypertensive patients aged ≥ 50 years were enrolled. The relationship between the severity of periodontitis and arterial stiffening (PP ≥ 60) was analyzed using multivariate logistic regression model. Moreover, the associations between pocket depth (PD) and clinical attachment loss (CAL) with arterial stiffening were investigated using multivariate logistic regression model and restricted cubic splines. Among the patients, 1223 (39%) exhibited no or mild periodontal disease, while 1447 (46%) and 495 (15%) were diagnosed with moderate and severe periodontal disease, respectively. Moderate and severe periodontitis were associated with higher odds of arterial stiffening compared to no/mild periodontitis in the fully adjusted model (moderate: OR 1.30 [95% CI 1.09–1.55], P = 0.004; severe: OR 1.35 [95% CI 1.05–1.73], P = 0.019; P for trend < 0.001). Higher quartiles of PD and CAL scores were significantly associated with greater odds of arterial stiffening (PD Q4 vs. Q1: OR 1.41 [95% CI 1.12–1.79], P = 0.004; CAL Q4 vs. Q1: 1.31 [95% CI 1.03–1.67], P = 0.030), with evidence of linear dose-response relationships (P non−linear association=0.114 for PD; P non−linear association=0.308 for CAL). Subgroup analyses showed that the association between periodontitis severity and arterial stiffening remained significant in participants without diabetes or chronic kidney disease. In hypertensive patients aged 50 years and over, periodontitis is associated with elevated PP, thus reinforcing the association between periodontitis and arterial stiffening. Screening and treating periodontitis may offer additional clinical benefits.